Characterization of stage‐specific tumor progression in TMPRSS2‐ERG (fusion)‐driven and non‐fusion‐driven prostate cancer in GEM models. Issue 7 (22nd April 2022) - Raina, Komal; Kant, Rama; Prasad, Ram R.; Kandhari, Kushal; Tomar, Munendra; Mishra, Neha; Kumar, Robin; Fox, Jennifer T.; Sei, Shizuko; Shoemaker, Robert H.; Chen, Yu; Maroni, Paul; et al.
Abstract: In the present study, we performed a comparative stage‐specific pathological and molecular marker evaluation of TMPRSS2‐ERG fusion and PTEN loss‐driven ( TMPRSS2‐ERG. Pten flox/flox ) versus non‐fusion‐driven prostate tumorigenesis ( Hi‐Myc ) in mice. Anterior, ventral, and dorsolateral prostates were collected from mice at different ages (or time points post‐ Cre induction). Results indicated that growth and progression of prostatic intraepithelial lesions to adenocarcinoma stages occurred in both mice models albeit at different rates. In the TMPRSS2‐ERG. Pten flox/flox mice, the initiation of tumorigenesis was slow, but subsequent progression through different stages became increasingly faster. Adenocarcinoma stage was reached early on; however, no high‐grade undifferentiated tumors were observed. Conversely, in the Hi‐Myc +/ − mice, tumorigenesis initiation was rapid; however, progression through different stages was relatively slower and it took a while to reach the more aggressive phenotype stage. Nevertheless, at the advanced stages in the Hi‐Myc +/ − mice, high‐grade undifferentiated tumors were observed compared to the later stage tumors observed in the fusion‐driven TMPRSS2‐ERG. Pten flox/flox mice. These results were corroborated by the stage specific‐pattern in the molecular expression of proliferation markers (PCNA and c‐Myc); androgen receptor (AR); fusion‐resultant overexpression of ERG; Prostein (SLC45‐A3); and angiogenesis marker (CD‐31). Importantly, there was a significant increase in immune cell infiltrations, which increased with the stage of tumorigenesis, in the TMPRSS2‐ERG fusion‐positive tumors relative to fusion negative tumors. Together, these findings are both novel and highly significant in establishing a working preclinical model for evaluating the efficacy of interventions during different stages of tumorigenesis in TMPRSS2‐ERG fusion‐driven PCa.